PRINSIP UNA VIA DALAM PENEGAKAN HUKUM DAN PENGUATAN PASAR MODAL INDONESIA - Prana, Andreas Eka; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
In an effort to strengthen law enforcement in the Indonesian Capital Market, regulators are granted the authority to choose whether to proceed with criminal proceedings in the Capital Market sector to the investigative stage or impose administrative sanctions (Una Via Principle) as stipulated in Article 100A Capital Market Section No. 4 of 2023 on the Development and Strengthening of the Financial Sector. This principle is an expansion of the ne bis in idem principle, providing legal certainty for perpetrators of criminal acts. However, this authority needs to be complemented with a strong structure and procedures to meet justice for perpetrators, victims, and the investor. This article will use Lawrence Friedman's perspective on the components of the legal system—Substance, Structure, and Culture—to address how the Una Via Principle can be applied in the enforcement of laws and the strengthening of the Indonesian Capital Market. This research is a normative legal study using legal theory and secondary data. The results of this research provide insights into important aspects that regulators need to consider in establishing clear guidelines for determining the handling of criminal cases, whether to proceed to the investigative stage or impose administrative sanctions on the perpetrators. This includes building solid coordination between regulators and other law enforcement agencies, strengthening procedures for imposing administrative sanctions, and continuously raising awareness of violations in the Capital Market among law enforcement agencies and the investing public.Keywords: Ne Bis In Idem, Una Via Principle, Capital Market Enforcement, Administrative Penal